(untitled) (Journal of Legal Studies, 2025)
Women’s underrepresentation in national legislatures is a persistent global concern. This study interrogates how political parties can promote greater women’s representation in Ghana’s Parliament. Using the mixed-methods approach, the paper combines a survey of 100 participants and in-depth interviews with six key informants. The findings reveal multiple challenges facing women in politics and identify mechanisms through which parties can help overcome these barriers. Internally, parties can introduce measures such as candidate quotas, reserved seats in safe constituencies, reduced filing fees, financial and material support, and capacity-building programs for aspiring female politicians. At the national level, legal reforms, including the implementation of the Affirmative Action (Gender Equity) Act (2024), are pivotal. While these strategies hold promise for increasing women’s parliamentary representation in Ghana, the study concludes that political parties must find a way to deal with internal opposition, as most stakeholders see these measures as undemocratic. The paper concludes that committed political party actions, coupled with supportive legal frameworks, are essential to achieving meaningful gains in women’s representation.